Highly reversible magnetocaloric effect in Gd5Si0.25Ge3.75 and Gd5Si0.5Ge3.5 under moderate magnetic fields for hydrogen liquefaction - E. Bykov; W. Liu; K. Skokov; F. Scheibel; O. Gutfleisch; J. Wosnitza; T. Gottschall (Communications Materials)
Abstract For magnetic cooling with the goal of hydrogen liquefaction, magnetocaloric materials with outstanding magnetic-entropy and adiabatic temperature changes (ΔS T and ΔT a d ) are required, covering the temperature range from liquid nitrogen to the condensation point of hydrogen at 20 K. Although second-order rare-earth-based intermetallic compounds show large ΔS T and ΔT a d near 20 K, their performance decreases drastically with increasing temperature. Here, compounds with first-order transition can be beneficial, if the reversibility of the magnetocaloric effect is ensured. In this work, we report that Gd5Si0.25Ge3.75 and Gd5Si0.5Ge3.5 exhibit highly reversible magnetocaloric effects near 55 and 80 K, respectively, in a magnetic field of 5 T despite significant thermal hysteresis. The high reversibility originates from the rapid shift of the transition temperature with magnetic field. Since superconducting coils are widely used to generate magnetic fields up to 5 T in existing magnetic refrigeration prototypes, this work proves that first-order magnetocaloric materials with significant thermal hysteresis can be promising candidates for hydrogen liquefaction in moderate magnetic fields.